Application of 2D‐DIGE to formalin‐fixed diseased tissue samples from hospital repositories: Results from four case studies. Issue 3 (6th March 2013) - Tanca, Alessandro; Pisanu, Salvatore; Biosa, Grazia; Pagnozzi, Daniela; Antuofermo, Elisabetta; Burrai, Giovanni P.; Canzonieri, Vincenzo; Cossu‐Rocca, Paolo; Re, Valli De; Eccher, Albino; Fanciulli, Giuseppe; Rocca, Stefano; et al.
<x xml:space="preserve">Abstract</x> Purpose In the recent past, the potential suitability of fixed samples to 2D‐DIGE studies has been demonstrated on model tissues, but not on "real‐world" archival tissues. Therefore, this study was aimed to assess the quality of the results delivered by 2D‐DIGE on samples retrieved from hospital tissue repositories. Experimental design Diseased and normal tissue samples (namely, human gastric adenocarcinoma and normal gastric tissue, human lung neuroendocrine tumors, canine mammary tubulo‐papillary carcinoma and normal mammary tissue, sheep liver with cloudy swelling degeneration and normal liver tissue) were retrieved from human and veterinary biorepositories and subjected to full‐length protein extraction, cyanine labeling, 2D‐DIGE separation, image analysis, MS analysis, and protein identification. Results Archival samples could be successfully subjected to 2D‐DIGE, providing maps of satisfactory resolution, although with varying pattern complexity (possibly influenced by preanalytical variables). Moreover, differentially expressed protein identities were consistent with the disease biology. Conclusions and clinical relevance 2D‐DIGE can support biomarker discovery and validation studies on large sample cohorts. In fact, although some information complexity is lost when compared to fresh‐frozen tissues, their vast availability and the associated patient information can considerably boost studies suffering limited sample availability or involving long‐distance exchange of samples.